Impacts of Polystyrene Nanoplastics on Fisheries Biology and Prospective Remediation Approaches in Aquatic Ecosystems - Jamil, Habiba; Kamal, Sidra; Lodhi, Muhammad Saeed; Wajee, Warda; Nidaullah, Hafiz; Kabir, Ayesha; Naseem, Farah; Mushtaq, Bushra; Ashraf, Nimra (Indus Journal of Bioscience Research, 2025)
Concerns regarding the effects of the ubiquitous environmental contaminant polystyrene nanoplastics (PS-NPS) on aquatic environments, specifically in fisheries biology, have been raised. Because of PS-NPs special characteristics, such as their tiny size, large surface area, and hydrophobic nature, they are highly bioavailable and can enter the food chain by being consumed by aquatic creatures. With an emphasis on fish physiology, behavior, and reproductive health, this review paper thoroughly examines how PS-NPS impacts aquatic life. Fish species have altered development rates, behavioral abnormalities, and decreased reproductive success as a result of PS-NPs’ toxicological effects, which include oxidative stress, inflammation, bioaccumulation, and disturbance of the endocrine and immunological systems, according to the review. The paper also addresses how PS-NPs interact with other environmental stresses, i.e., pesticides and heavy metals, which might increase their toxicity. The review also emphasizes the difficulties in determining PS-NPs’ whole ecological effect because of the intricacy of their interactions in various aquatic habitats. Additionally included are potential remediation techniques to lessen PS-NPs’ negative effects on aquatic ecosystems. These include novel techniques, including the use of nanomaterials for PS-NP sorption, bio-based remediation employing microbes and algae, and physical techniques like sedimentation and filtration. To address the rising danger presented by PS-NPs and safeguard fishery resources, the study highlights the necessity of multidisciplinary research, regulatory frameworks, and coordinated management techniques. The article’s conclusion offers suggestions for further study targeted at creating long-term strategies to reduce PS-NP contamination in aquatic environments.